1992
DOI: 10.1016/0094-1190(92)90003-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-selection and internal migration in the United States

Abstract: The Naiiond Lnngil>dind S.wcys (NLs) program supporls m:my sludic$ designed 10 increase "ndcrwandimg of tic labxm market and rncih.ds of dtiru colkxdon The Oi.s.curxion Papers scriw inco~raks some of tie research coming OU1of [he program.Many of the papers in his series have bum dclivcrcd m find mporu+ uxnmissioncd as part of an cxuanmral grant program, under which grams arc aw.wdcd lhrough a competitive process. The series is inmndcd 10 circula!c fit findings 10 inlcrcsmd readers wilhm and oulside the Bureau … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
263
1
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(285 citation statements)
references
References 21 publications
14
263
1
5
Order By: Relevance
“…Firstly, migration is subject to self-selection, and secondly, migrants appear more "employable" than natives. Borjas, Bronars, and Trejo (1992) nd that within the US, migrants in 1986 had a three percent higher educational attainment on average than non-movers, similar to Shioji (2001). Dolado et al (1994) report that international migrants only bear around 80% of human capital compared to natives.…”
Section: Introductionmentioning
confidence: 49%
“…Firstly, migration is subject to self-selection, and secondly, migrants appear more "employable" than natives. Borjas, Bronars, and Trejo (1992) nd that within the US, migrants in 1986 had a three percent higher educational attainment on average than non-movers, similar to Shioji (2001). Dolado et al (1994) report that international migrants only bear around 80% of human capital compared to natives.…”
Section: Introductionmentioning
confidence: 49%
“…Using data from the National Longitudinal Survey of Youth (NLSY) for 1979 to 1986, Borjas et al (1992) found that interstate differences in the returns to skills are an important determinant of the migration decision. Regions that pay higher returns to skills attract more skilled workers than regions that pay lower returns.…”
Section: Aggregate Characteristicsmentioning
confidence: 99%
“…These datasets include the CPS (Basker, 2003, andBlank, 1988), the decennial Census data (Wozniak, 2010;Malamud and Wozniak, 2010;Whisler et al, 2008;Herzog and Schlottmann, 1986), the Integrated Public Use Microdata Series, based on Census data Schlottmann, 1983, andRosenbloom andSundstrom, 2003), the NLSY (Haurin and Haurin, 1988;Yankow, 2002Yankow, /2003Yankow, , 2003Borjas et al, 1992), and the PSID (Rodgers andRodgers, 2000, andBlackburn et al, 2010). Additionally, studies have used the Social Security Administration's Continuous Work History Sample (Greenwood, 1986) and data from the IRS (Davies et al, 2001).…”
Section: Datamentioning
confidence: 99%
“…9 Because w A and w B are correlated through the correlation structure in ; it is easier to work with the orthogonal components w + A ; w + B of (w A ; w B ) in the value function iteration.…”
Section: Numerical Aspectsmentioning
confidence: 99%